Examination of Demographics and Chronic Health Condition Management in an Underserved Population at a Pro Bono Physical Therapy Clinic - Creps, James; Kaartinen, Mia; Diebold, Kayla (Journal of Student-Run Clinics, 2017)
Background: The purpose of this study was to identify and describe the demographic information of the patient population at a student-run physical therapy pro bono clinic. We hypothesized this patient population would present with more chronic health conditions that are either unmanaged or under-managed compared with Genesee County, Michigan. Methods: New patients were asked to complete a 47-question survey on demographic information, past medical history, and social history. Vital signs were also recorded. Frequency tables were run to determine the health needs in this patient population. Self-report of hypertension, diabetes, and depression was compared to self-reported medications to determine medical management of the conditions. Results: Some patients report taking medications for these conditions, but many individuals are not medically managing these conditions. Conclusions: With this information, clinicians can better create programs that meet the specific needs of this patient population including fitness programs, chronic disease management education, and pain management programs.